Spoligotype Variation of Mycobacterium tuberculosis Strains Prevailing in Korea - Seung-Eun Song; Dong Hyeok Kim; Seong-Han Kim; Mi-Sun Park; Sang-Hee Park; Kil-Soo Lee (Canadian Journal of Infectious Diseases and Medical Microbiology)
Tuberculosis (TB) is an ongoing global health problem, including in South Korea. To manage TB efficiently, it is necessary to understand the epidemiology, transmission route, and characteristics of prevailing Mycobacterium tuberculosis strains. In this study, we investigated microevolutions over time in the spoligotype patterns of M. tuberculosis isolated from TB patients in Korea. We collected 1,055 clinical M. tuberculosis isolates from 16 provinces in Korea from 1994 to 2006 and analyzed them by spoligotyping. We observed 26 subfamilies, including two large predominant families: a Beijing family (72.7%) and the T family (19.1%). Specifically, the abundance of spoligotype SIT269 from the Beijing-like subfamily significantly increased in the 2000s relative to the 1990s in Korea. This study provides an overview of the M. tuberculosis genotype trends over time in Korea. These data also indicate that we should consider the influence of the newly growing SIT269 subtype identified in the Beijing family.